Effect of sires’ expected progeny difference for scrotal circumference and juvenile ADG on the puberty of crossbred beef heifers - Barroso, José Paulo Roman; de Castro Ferraz Junior, Marcos Vinicius; Oliveira, Gabriela Bagio; Miszura, Alexandre Arantes; Bertoloni, Analisa Vasques; Martins, André Storti; Baggio, Marcelo; Polizel, Daniel Montanher [UNESP]; Biava, Janaina Socolovski [UNESP]; Ferreira, Evandro Maia; Pires, Alexandre Vaz (Springer Nature, 2023)
The early attainment of puberty in heifers is essential for the profitability of the cow-calf farm. This study aimed to evaluate the impact of juvenile average daily gain (ADG) and sire’s expected progeny difference (EPD) on puberty of crossbred beef heifers. Sixty Angus × Nellore heifers early weaned (age = 102 ± 4.3 d; initial BW = 103 ± 4.7 kg) were used in a 2 × 2 factorial arrangement. The factor 1 was the sire’s EPD for scrotal circumference, in which heifers born from sires with positive EPD were considered precocious (P), and heifers born from sires with negative EPD were considered non-precocious (NP). The factor 2 was the high (HG; ADG = 0.9 kg; ad libitum) and medium ADG (MG; ADG = 0.7 kg) from 3rd to 7th month of age (1st phase). After 1st phase until puberty, all heifers were fed ad libitum (2nd phase). Statistical analysis was performed by SAS. There was an interaction between factors for DMI in the 1st phase (P = 0.02), which PHG heifers had higher DMI than NPHG. There was no effect on puberty rate, BW, age and BCS at puberty comparing HG vs. MG. However, favorable sires’ EPD for scrotal circumference induced a higher proportion of puberty (P 87% vs. NP 59%) at 15 months of age. Thus, the ADG in juvenile age did not affect puberty rate, but sires with positive EPD increased puberty rate of Angus × Nellore heifers in heifers fed a high gain diet.
Keywords: Compensatory growth; IGF-1; Insulin; Puberty rate; Sexual precocity